2007
DOI: 10.1111/j.1471-4159.2007.05091.x
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord degeneration in C57BL/6N mice following induction of experimental parkinsonism with MPTP

Abstract: We examined neurodegeneration in spinal cord (SC) and role of such extra‐nigral degeneration in MPTP‐induced experimental parkinsonism in C57BL/6N mice. HPLC‐photodiode array analysis confirmed presence of the active neurotoxin MPP+ in SC after single injection of MPTP (25 mg/kg, i.p.). Mitochondrial enzyme monoamine oxidase‐B (MAO‐B) responsible for in vivo conversion of MPTP to MPP+ was inhibited in SC by pre‐treatment with l‐deprenyl, a specific inhibitor of MAO‐B. Besides in vitro conversion of MPTP to MPP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 63 publications
4
28
0
Order By: Relevance
“…The report showed that the presence of the 1-methyl-4-phenylpyridinium ion (MPP + ) form in the synaptosomal fraction of the spinal cords following MPTP intoxication, along with monoamine oxidase-B (MAO-B) activity and DAT immunolocalization in the spinal cord neurons, resulted from the transformation of MPTP to MPP + in the spinal cords. This transformation is well recognized as the initial reaction in the induction of nigrostriatal degeneration by MPTP intoxication, and finally may result in spinal cord neuro-intoxication through MPTP intoxication in the report (Samantaray et al, 2008). In actuality, neuronal death was observed in the spinal cords of pre-symptomatic mice following the intraperitoneal MPTP intoxication, which suggested extra-nigral degeneration by MPTP, at least in part, in the spinal cord (Samantaray et al, 2008).…”
Section: Up-down-regulated Genes By Mptp and Acupuncturementioning
confidence: 89%
See 4 more Smart Citations
“…The report showed that the presence of the 1-methyl-4-phenylpyridinium ion (MPP + ) form in the synaptosomal fraction of the spinal cords following MPTP intoxication, along with monoamine oxidase-B (MAO-B) activity and DAT immunolocalization in the spinal cord neurons, resulted from the transformation of MPTP to MPP + in the spinal cords. This transformation is well recognized as the initial reaction in the induction of nigrostriatal degeneration by MPTP intoxication, and finally may result in spinal cord neuro-intoxication through MPTP intoxication in the report (Samantaray et al, 2008). In actuality, neuronal death was observed in the spinal cords of pre-symptomatic mice following the intraperitoneal MPTP intoxication, which suggested extra-nigral degeneration by MPTP, at least in part, in the spinal cord (Samantaray et al, 2008).…”
Section: Up-down-regulated Genes By Mptp and Acupuncturementioning
confidence: 89%
“…These observations imply that Ube2l6 plays a role in the ISGylation of proteins which is part of many cellular pathways, but may not be involved in the conventional proteasome-mediated protein degradation. It was shown that MPTP intoxication induces the degeneration of dorsal and ventral horns in the spinal cords of mice (Samantaray et al, 2008). The report showed that the presence of the 1-methyl-4-phenylpyridinium ion (MPP + ) form in the synaptosomal fraction of the spinal cords following MPTP intoxication, along with monoamine oxidase-B (MAO-B) activity and DAT immunolocalization in the spinal cord neurons, resulted from the transformation of MPTP to MPP + in the spinal cords.…”
Section: Up-down-regulated Genes By Mptp and Acupuncturementioning
confidence: 99%
See 3 more Smart Citations